Pemaknaan Kesetaraan Gender oleh Penonton dalam Film Mulan - Audhira Nurul Fadilla; Wijaksono, Dimas Satrio (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
The rise of the issue of gender equality that has occurred until now is still a very important discussion in the society. The issue is then reviewed into an interesting story full of meaning in a film. Mulan is one of the films that raises the theme of gender equality and shows the contrast of gender inequality in society. This research itself intends to find out how the audience's reception regarding the message of gender equality embedded in the Mulan film. This research used a descriptive qualitative method through the Stuart Hall reception analysis approach. This research aims to analyze the position of the audience in interpreting the message of gender equality in the Mulan film according to three (3) readings of audience’s position through Stuart Hall’s theory of reception analysis. In this case, the three positions in question are: Dominant Reading, Negotiated Reading, and Oppositional Reading. The results showed that the reading of the audience’s position was in Dominant Reading. This position revealed how all informants as audiences could accept the meaning of the message conveyed in the Mulan film regarding the gender equality, although with various different perspectives. The position of the audience’s meaning was analyzed by looking at the emerging themes based on data from Focus Group Discussion (FGD) session, including: scenes, dialogues or verbal messages, environmental influences, thoughts, and message meanings. Keywords: Reception Analysis, Film, Gender Equality